Students’ Alienation from Learning Activity: Some Insights from High-School Seniors’ Study in Lithuania - Labokas, Juozapas (Journal of Education Culture and Society, 2024)
Aim. The aim of this research is to define the causes of student alienation from learning in the high-school seniors (aged 18-19) population (n=227) of three randomly chosen Lithuanian high schools. Methods. In this analysis, we use a mixed-method approach. In the first research phase, we used the quantitative school alienation measurement instrument proposed by Julia Morinaj et al. (2019), which helped to locate the extreme cases of alienation and non-alienation in research schools. In the second phase, both research groups (7 alienated and 7 non-alienated) were interviewed individually using qualitative semi-structured interviews. Data gathered from interviews was processed using the thematic analysis method, proposed by Virginia Braun and Victoria Clarke (2012). Results. The results confirmed earlier theoretical presumptions that defined school alienation as a multifaceted and case-sensitive phenomenon. The qualitative approach has revealed its’ multi-dimensional nature illustrated by students’ experiences. Conclusion. Alienation from learning could be interpreted as a level of learning actualisation that is perceived by the student, which could be influenced by individual and/or structural factors, such as individual attitude towards learning, learning styles, parental influence, teacher and classmates support, future career/academic plans and expectations. Cognitive value. According to our literature analysis made prior to the research, it is the first attempt to analyse school alienation using a mixed-method approach, which combines verified quantitative and qualitative instruments. It is hoped that this research will be of benefit for the further conceptualisation of the school alienation phenomenon and could be a practical guide in everyday pedagogical practice.